Célula madre: narraciones para nuevas transformaciones - Blanco, Daniel R. (2024)
Are geological ages, those that define the world, just a series of palimpsests? The writings over the writings made out of sediments… If so, I can rewrite spaces, turn them into something more queer, more abstract, that could allow other types or relations to be with the world. It takes months to collect as many branches to be able to weave a mountain. And I began to feel that I understood the time of the trees. Those dead branches, that had been written as “dead” from a human point of view, I can name them “new lives”, make a collaboration with them to create a new sort of landscape, one that redefines the binaries that have been dominating the world, to allow for the creation of new and different spaces. I can make a mountain that traces some sort of coordinates of a world constructed from a collaboration between culture and nature. A mountain that, perhaps, in the centuries to come, will be covered by sediments that will follow the structure of the dead branches, to create artificial landscapes. Perhaps this is a space in which, finally, queer identities (those that had been classified as anti-natural), and the same nature (that also has been forced into binary categories), can reconcile. This project, which is in itself a hybrid project that encompasses an art installation, land art, and a novel, in which different creative processes that think the ways in which the world is narrated can interconnect, looks to find new ways of storytelling, and in doing so, new ways of inhabiting the territory, the space, and new ways of giving other kinds of lives and other types of spaces the possibility to exist.